Effect of prolactin acting on the coeliac ganglion via the superior ovarian nerve on ovarian function in the postpartum lactating and non-lactating rat - Vallcaneras, Sandra (2013)
Whether prolactin (PRL) has a luteotrophic or luteolytic effect in the rat ovary depends on the nature of the corpora lutea present in the ovaries and the hormonal environment to which they are exposed. The aim was to investigate the effect of PRL acting on the coeliac ganglion (CG) on the function of the corpora lutea on day 4 postpartum under either lactating or non-lactating conditions, using the CG–superior ovarian nerve–ovary system. The ovarian release of progesterone (P), estradiol, PGF2α, and nitrites was assessed in the ovarian compartment at different incubation times. Luteal mRNA expression of 3β-HSD, 20α-HSD, aromatase, PGF2α receptor, iNOS, Bcl-2, Bax, Fas and FasL was analysed in the corpus luteum of pregnancy at the end of the experiments. Comparative analysis of control groups showed that the ovarian release of P, nitrites, and PGF2α, the expression of PGF2α receptor, and the Bcl-2/Bax ratio were lower in non-lactating rats, with increased release of estradiol, and higher expression of aromatase, Fas and FasL, demonstrating the higher luteal functionality in ovaries of lactating animals. PRL added to the CG compartment increased the ovarian release of P, estradiol, nitrites and PGF2α, and decreased the Bcl-2/Bax ratio in non-lactating rats; yet, with the exception of a reduction in the release of nitrites, such parameters were not modified in lactating animals. Together, these data suggest that the CG is able to respond to the effect of PRL and, via a neural pathway, fine-tune the physiology of the ovary under different hormonal conditions.